PENGARUH CELEBRITY ENDORSEMENT DAN BRAND IMAGE TERHADAP MINAT BELI KONSUMEN PADA SCARLETT WHITENING - Hutabarat, Feiny; Riski, Defia (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
The large number of beauty products in Indonesia can increase competition between the cosmetics industry. Therefore, companies compete to control market share and develop marketing strategies to increase consumer buying interest. The aim of the research is to determine and analyze the influence of Celebrity Endorsement and Brand Image on the impulse purchase interest of consumers for Scarlett Whitening products in Bandarlampung. This type of research is quantitative with a descriptive analysis method. The sampling technique in the research used purposive sampling. The data collection method uses a questionnaire and variable measurement uses four Likert scales. The sample in this study was 120 respondents. The data analysis techniques used include validity and reliability tests. The data analysis used is multiple linear regression analysis and hypothesis testing in the form of T Test, F Test and Coefficient of Determination Test. The research results show that simultaneously, the Celebrity Endorsement and Brand Image variables have a positive and significant effect on Purchase Interest in Scarlett Whitening in Bandarlampung. Partially, the Celebrity Endorsement variable has a significant influence on Purchase Interest and the Brand Image variable also has a significant influence on Purchase Interest.